Prevalence and risk factors for youth suicidality among perinatally infected youths living with HIV/AIDS in Uganda: the CHAKA study - Rukundo, Godfrey Zari; Mpango, Richard Stephen; Ssembajjwe, Wilber; . Gadow, Kenneth D; Patel5, Vikram; Kinyanda, Eugene (Child Adolesc Psychiatry Ment Health, 2020)
Background: Research from high income countries indicates that suicide is a major mental health care concern and a leading cause of preventable deaths among children and adolescents. Proper assessment and management of youth suicidality is crucial in suicide prevention, but little is known about its prevalence and associated risk factors in Sub-Saharan Africa. In low income countries there is an increased risk of suicide among persons with HIV/AIDS even in the presence of the highly active antiretroviral therapy. Objective: To determine the prevalence of and risk factors for youth suicidality among perinatally infected youth living with HIV/AIDS in Uganda. Methods: We studied 392 HIV positive children (5–11 years) and adolescents (12–17 years) and their caregivers in Kampala and Masaka districts. Caregivers were administered the suicide assessment section of the MINI International Psychiatric Interview. Socio-demographic characteristics, psychiatric diagnoses, and psychosocial and clinical factors were assessed and suicidality (suicidal ideation and or suicidal attempt) was the outcome variable. Logistic regression was used to calculate odds ratios adjusting for study site and sex at 95% confidence intervals. Results: Caregivers reported a suicidality rate of 10.7% (CI 8–14.1) in the past one month with higher rates among urban female (12.4%, CI 8.6–17.7) than male (8.7%, CI 5.4–13.8) youth. Lifetime prevalence of attempted suicide was 2.3% (n = 9, CI 1.2–4.4) with the highest rates among urban female youth. Among children, caregivers reported a lifetime prevalence of attempted suicide of 1.5%. The self-reported rate of attempted suicide in the past month was 1.8% (n = 7, CI 0.8–3.7) with lifetime prevalence of 2.8% (n = 11, CI 1.6–5.0). The most common methods used during suicide attempts were cutting, taking overdose of HIV medications, use of organophosphates, hanging, stabbing and self-starvation. Clinical correlates of suicidality were low socioeconomic status (OR = 2.27, CI 1.06–4.87, p = 0.04), HIV felt stigma (OR = 2.10, CI 1.04–3.00, p = 0.02), and major depressive disorder (OR = 1.80, CI 0.48–2.10, p = 0.04). Attention-deficit/hyperactivity disorder was protective against suicidality (OR = 0.41, CI 0.18–0.92, p = 0.04). Conclusion: The one-month prevalence of suicidality among CA-HIV was 10.7%.
Keywords: Suicide; Suicidality; Suicidal attempt; Suicidal ideation; Youths; HIV